Wittgensteinian Network and Wittgensteinian Oracle. Two humanistic-digital tools in and beyond lexicological enquiry - Filippo Mosca (Umanistica Digitale)
This paper aims to illustrate the functioning of Wittgensteinian Network [WN] and Wittgensteinian Oracle [WO]. [WN] and [WO] are two websites designed to assist scholars and researchers in exploring and deepening the philosophy of Ludwig Wittgenstein. [WN] is a website designed to facilitate the lexicological investigation of key terms of the so-called context principle in the texts of the ‘early Wittgenstein’. [WO] is a tool that uses artificial intelligence, and specifically GPT technology, to explore Wittgenstein's philosophical work. More specifically, [WO] is a website that consists of a series of customised GPT models designed to answer questions related to the specific manuscript or typescript of Wittgenstein's Nachlass to which they are associated. The aim of the paper is to highlight both the potential and limitations of these two humanistic digital tools in the study of a particular complex idea - the context principle - and of its development within Wittgenstein's philosophical thought.